Penerapan Model Pembelajaran Kartu Arisan untuk Meningkatkan Prestasi Belajar Matematika Siswa pada Materi Perbandingan - Surya, Liliana Inggrida; Sumadji, Sumadji; Suwanti, Vivi (Jurnal Tadris Matematika, 2019)
The purpose of this research is to find out how the application of the Arisan Card learning model improve students' mathematics learning achievement. This research is a Classroom Action Research. Subjects of this study were students of class VII-B SMP PGRI 6 Malang. Data collection procedures in this study are tests, observations and field notes. The results of this study are the completeness of students in the activities of the first cycle 60.71% and the second cycle 89.28% and the observation results of the first cycle teacher, observer I 76.06%, observer II 75.21% and second cycle observer I 88.03% observer II 85.47% and for the observations of students I observer I cycle 73.50%, observer II 70.94% and second cycle observer I 85.47%, observer II 84.61%. Based on the results of the study, the Arisan Card learning model?s steps are: 1) dividing students into groups by emphasizing the circular sitting formation; 2) distribute the answer papers to each group; 3) put the questions into arisan bottle and then shaken and poured; 5) asks one of the groups holding the answer paper to move forward and present it to the class; 6) if the answer is correct then the group gets points.